Contribution of the social work to the understanding on the conditioning of the free time of children attending the 1st cycle: https://doi.org/10.53809/2021-01-TS-n.1-208-223 ("Temas Sociais" Journal, 2021)
The following article intends to clarify the importance of the Social Work for the understanding of the conditioning of children's free time that attend the 1st cycle in the parish of São Domingos de Rana. A qualitative methodological approach was used, resorting to an explorative interview, compiled by a sample of visions and knowledges of essential interdisciplinary areas for the established goals. The obtained results demonstrated a development of family structures, with conjugality marked by the paradox of the existence of affection and quality time between parents and children. The sociodemographic features of families residents in the parish are highlighted by its origin and characterised by a heterogeneous population, active in society and with economic and social stability.  The institutions that respond to leisure time in the parish are classified by schooling, with the school becoming more representative, in response to the needs of parents. The family is highlighted in an educational context and in a labour market context, in the sense that its articulation conditions their performance.
Keywords: social work; family; school; childhood; free time